Metabolites and biological activities of Thymus zygis, Thymus pulegioides, and Thymus fragrantissimus grown under organic cultivation - Fernandes Afonso, Andrea Luísa (2018)
Thymus plants are marketed for diverse usages because of their pleasant odor, as well as high nutritional value and wealth of health-promoting phytochemicals. In this study, Thymuszygis, Thymuspulegioides, and Thymusfragrantissimus grown under organic cultivation regime were characterized regarding nutrients and phenolic compounds. In addition, the antioxidant and antibacterial properties of these species were screened. The plants were particularly notable for their high K/Na ratio, polyunsaturated fatty acids content and low omega-6/omega-3 fatty acids ratios, which are valuable features of a healthy diet. Caffeic acid and/or its derivatives, mainly rosmarinic acid and caffeoyl rosmarinic acid, represented the majority of the phenolic constituents of these plants, although they were less representative in T. pulegioides, which in turn was the richest in flavones. The latter species also exhibited the highest antioxidant capacity (DPPH● EC50 of 9.50 ± 1.98 μg/mL and reducing power EC50 of 30.73 ± 1.48 μg/mL), while T. zygis was the most active towards Gram-positive and Gram-negative bacteria. Overall, the results suggest that the three thyme plants grown in organic farming are endowed with valuable metabolites that give them high commercial value for applications in different industries.